House dust mite allergen level and allergen sensitization as risk factors for asthma among student in Central Jakarta (Medical Journal of Indonesia, 2006)
This study is a community-based study to get an overview about House Dust Mite (HDM) allergen level, allergen sensitization as risk factors of asthma. This is a cross-sectional study on 3,840 students from 19 junior high schools, aged 13-14 years. All of the respondents filled out the International Study on Asthma and Allergy in Children (ISAAC) questionnaire. Of 3840 respondents, 288 (7.5%) were assigned to asthma group (experience wheezing during the last 12 months). The skin prick test was performed on 207 respondents and the house dust mite was collected from 135 respondents. Of 2601 respondents in non-asthma group, the skin prick test was randomly performed on 274 respondents and the house dust mite was collected from 165 respondents. There is no significant difference on HDM allergen concentration for Der p1, Der f1 or Group I between asthma and control group. The risk of asthma was caused especially by sen D.pteronyssinus (crude odds ration (OR): 12.68, 95% confidence interval (CI): 7.50-21.44), D.farinae (OR: 10.50, CI: 6.35-17.34) and cockroach allergen (OR:5.57, CI:3.44-9.01). The risk for asthma was not correlated with the level of house dust mite allergens but its sensitization. In conclusion, sensitization to HDM and cockroach allergen should be concerned in order to reduce risk and prevalence of asthma. (Med J Indones 2006; 15:55-9)Keywords: house dust mite, allergen sensitization, asthma, risk factor